2021
DOI: 10.1186/s12912-021-00670-8
|View full text |Cite
|
Sign up to set email alerts
|

The item network and domain network of burnout in Chinese nurses

Abstract: Background As a common social phenomenon, nurses’ occupational burnout has a high incidence rate, which seriously affects their mental health and nursing level. The current assessment mostly uses the total score model and explores the influence of external factors on burnout, while the correlation between burnout items or dimensions is less explored. Ignoring the correlation between the items or dimensions may result in a limited understanding of nurse occupational burnout. This paper explores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 58 publications
2
14
1
1
Order By: Relevance
“…At present, most of the research on work alienation and ego depletion is based on the latent variable model, ignoring the complex interaction between the items of the two variables (Wu et al, 2021). Therefore, this paper intended to use the advantages of network analysis to provide new perspectives for the study of the relationship between work alienation and ego depletion in more detail and to make more targeted clinical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…At present, most of the research on work alienation and ego depletion is based on the latent variable model, ignoring the complex interaction between the items of the two variables (Wu et al, 2021). Therefore, this paper intended to use the advantages of network analysis to provide new perspectives for the study of the relationship between work alienation and ego depletion in more detail and to make more targeted clinical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Several advantages of network analysis make it a suitable analytical technique for the current study. First, previous studies have explored the internal structures of MW and burnout, respectively, with network analysis and concluded that network analysis is a valuable tool for deepening understanding of these two psychological constructs ( 28 , 29 ). Second, existing research mainly focused on examining the relationship between MW and burnout at a construct level ( via sum scores).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the attitude and view may interact with each other (i.e., the interactivity), and some attitude or view may be crucial for the marital satisfaction (i.e., there is one central element). In fact, similar assumptions have been confirmed in an increasing number of studies, such as decision-making competence (Peng et al, 2020), resilience (Briganti & Linkowski, 2020), well-being (Stochl et al, 2019), stigma (Wei et al, 2020), burnout (Wu et al, 2021), intolerance of uncertainty (Bottesi et al, 2020), and dark personality traits (Marcus et al, 2018). All of these studies have investigated the construct's internal structure and central elements, which adopted a new and promising approach, namely network analysis.…”
Section: Introductionmentioning
confidence: 69%